Financial development and resource curse: panel threshold evidence - Sarmidi, Tamat; Law, Siong Hook; Mohd Salleh, Norlida Hanim (School of Economics, Faculty of Economics and Management, Universiti Kebangsaan Malaysia, 2012)
This paper examines the relationship between natural resources and financial development using non-dynamic panel threshold analysis. This paper contributes to the natural resource curse (NRC) literature in three main areas. First, we focus on the relationship between resource abundance and financial development which is rarely discussed in the NRC literature. Second, we suppose that the relationship between resource abundance and financial development may not necessarily monotonic. It is because many relationships between economic variables are not linear throughout time or space due to natural cycle of economics forces. Therefore it might be the case that at one level of natural resources, the effect to financial development is negative while at another level the effect might be positive. Third, development of social capital seems to be an important mechanism for nullifying the NRC paradox. Employing an endogenous non-dynamic panel threshold estimation technique, we find four important results; first, the relationship between natural resource and financial development is non-monotonic; second, human development contributes positively to the financial development; third, the existence of NRC hypothesis in the finance-resource nexus is depending on the level of human development. Low human development economies experience negative contribution of natural resources to financial development, while this relationship is not applicable for high human development economies.